Involvement of plastid, mitochondrial and nuclear genomes in plant-to-plant horizontal gene transfer - Sánchez Puerta, María Virginia (2014)
This review focuses on plant-to-plant horizontal gene transfer (HGT) involving the three DNA-containing cellular compartments. It highlights the great incidence of HGT in the mitochondrial genome (mtDNA) of angiosperms, the increasing number of examples in plant nuclear genomes, and the lack of any convincing evidence for HGT in the well-studied plastid genome of land plants. Most of the foreign mitochondrial genes are non-functional, generally found as pseudogenes in the recipient plant mtDNA that maintains its functional native genes. The few exceptions involve chimeric HGT, in which foreign and native copies recombine leading to a functional and single copy of the gene. Maintenance of foreign genes in plant mitochondria is probably the result of genetic drift, but a possible evolutionary advantage may be conferred through the generation of genetic diversity by gene conversion between native and foreign copies. Conversely, a few cases of nuclear HGT in plants involve functional transfers of novel genes that resulted in adaptive evolution. Direct cell-to-cell contact between plants (e.g. host-parasite relationships or natural grafting) facilitate the exchange of genetic material, in which HGT has been reported for both nuclear and mitochondrial genomes, and in the form of genomic DNA, instead of RNA. A thorough review of the literature indicates that HGT in mitochondrial and nuclear genomes of angiosperms is much more frequent than previously expected and that the evolutionary impact and mechanisms underlying plant-to-plant HGT remain to be uncovered.